Assessment Literacy: Reconceptualizing the process of perception - Muradkasimova, Kamola Shukhratovna (The Lingua Spectrum, 2026)
The following research was undertaken with the help of two data collection methods: qualitative and quantitative. Qualitative method helped to identify the perception of teachers on student assessment. Quantitative method was used as test with authentic and contextualized scenarios. The research was conducted with 103 English as foreign language (EFL) teachers from three language universities in Uzbekistan. Through, conducted research methods we have found 1) the teachers LAL profile and 2) the need for stronger training in assessment practice than in theory. These two findings can be explained by the gap between subject matter knowledge and pedagogy of assessment. Findings of this study contribute to our understanding of LAL development in assessment training for language teachers in pre -service and in-service teacher programs. The consistency in developing teachers’ language assessment literacy can be reached by well-developed assessment course in practicing classroom assessment.